THE RECOGNITION OF THE LEGAL STANDING OF ENVIRONMENTAL ORGANIZATIONS IN INDONESIA - Fajar Winarni (Fakultas Hukum Universitas Gadjah Mada, 2013)
This study aims to identify and assess the recognition of the legal standing of environmental organizationsin Indonesia as well as to identify and assess the suitability of the use of legal standing environmental organizations with Article 92 of Law Number 32 of 2009 on the Protection and Environmental Management (UUPPLH). This research is normative. Data were analysed by descriptive qualitative. Research showsthat environmental organizations are very effective push policy reforms and changes attitudes and behaviour of government and business. Legal standing not just filed to the court, but also to the Administrative Court and the Constitutional Court. Penelitian ini bertujuan untuk mengetahui dan mengkaji diakuinya legal standing organisasi lingkungan hidup di Indonesia serta untuk mengetahui dan mengkaji kesesuaian penggunaan legal standing organisasi lingkungan hidup dengan Pasal 92 Undang-Undang Number 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup (UUPPLH). Penelitian ini merupakan penelitian normatif. Data dianalisis secara deskriptif kualitatif. Penelitian menunjukkan bahwa organisasi lingkungan hidup sangat efektif mendorong pembaruan kebijakan dan mengubah sikap serta perilaku Pemerintah dan pelaku usaha. Legal standing diajukan tidak hanya ke Pengadilan Negeri, namun juga ke PTUN dan Mahkamah Konstitusi.